Meta-Analysis: Effects of Smoking, Alcohol Consumption, and Low Physical Activity on Osteoporosis in Adults - Muhammad Fahrezi Al Ghifari; Yulia Himawati; Aem Ismail; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Osteoporosis is a systemic skeletal disease characterized by low mineral bone mass and microarchitectural deterioration of bone tissue. This study aims to analyze the effect of smoking, alcohol consumption, and low physical activity on osteoporosis in adults.Subjects and Method: This was a meta-analysis study using the PICO format. Population: Adults, Intervention: Smoking, Alcohol Consumption, Low Physical Activity, Comparison: No Smoking, No Alcohol Consumption, High Physical Activity, Outcome: Osteoporosis. Articles were searched using online databases such as PubMed, Google Scholar, Science Direct. The search for articles using the keywords